A Qualitative Review of Balance and Strength Performance in Healthy Older Adults: Impact for Testing and Training - Urs Granacher; Thomas Muehlbauer; Markus Gruber (Journal of Aging Research)
A continuously greying society is confronted with specific age-related health problems (e.g., increased fall incidence/injury rate) that threaten both the quality of life of fall-prone individuals as well as the long-term sustainability of the public health care system due to high treatment costs of fall-related injuries (e.g., femoral neck fracture). Thus, intense research efforts are needed from interdisciplinary fields (e.g., geriatrics, neurology, and exercise science) to (a) elucidate neuromuscular fall-risk factors, (b) develop and apply adequate fall-risk assessment tools that can be administered in clinical practice, and (c) develop and design effective intervention programs that have the potential to counteract a large number of fall-risk factors by ultimately reducing the number of falls in the healthy elderly. This paper makes an effort to present the above-raised research topics in order to provide clinicians, therapists, and practitioners with the current state-of-the-art information.